2018
DOI: 10.1016/j.sdentj.2017.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing private dental clinics in Riyadh City, Saudi Arabia

Abstract: Private dental clinics in Riyadh city are operated mainly by Non-Saudi dentists. Moreover, there is still a need for more female dentists and dental specialists. There are areas in Riyadh city that lack private dental clinics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 9 publications
(9 reference statements)
1
6
0
Order By: Relevance
“…Most of the respondents had 1–5 years of experience due to a considerable increase in the number of graduate dentists in recent years. [ 11 12 ] Overall, 93.4% of the practitioners performed endodontic practice in private clinics were GDPs which is in agreement with the findings reported by Al-Fouzan in Saudi Arabia. [ 6 ]…”
Section: Discussionsupporting
confidence: 86%
“…Most of the respondents had 1–5 years of experience due to a considerable increase in the number of graduate dentists in recent years. [ 11 12 ] Overall, 93.4% of the practitioners performed endodontic practice in private clinics were GDPs which is in agreement with the findings reported by Al-Fouzan in Saudi Arabia. [ 6 ]…”
Section: Discussionsupporting
confidence: 86%
“…The current study shows that private dental clinics are not evenly distributed geographically in Al-Ahsa. A previous study shows a similar trend in Riyadh city [7]. The location of the dental centers was found to be the main factor discouraging patients from receiving dental care [11,12].…”
Section: Discussionmentioning
confidence: 57%
“…Results also indicate that 43% of dentists in Al-Ahsa are female. An earlier study showed that most of the dentists' workforce in Riyadh city were male [7], The social and religious factors which dominate Saudi society may play a critical factor in a patient's decision to choose a private dental clinic. It clear that more female dentists are drawn to work in private clinics.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations